Mars (1564): the initial archaeological investigations of a great 16th‐century Swedish warship. (1st March 2017) - Eriksson, Niklas; Rönnby, Johan
Abstract : Before the Swedish warship Mars exploded and sank in action against a combined Danish and Lübeckian fleet in 1564, it was one of the largest ships in the world. In 2011 the wreck was relocated off the island of Öland in the Baltic Sea. Thanks to the favourable conditions in the brackish water, about two thirds of the hull is preserved on the sea bottom, including the stern with the large sterncastle. The aim of this article is to present initial archaeological observations and results of work since 2011. We briefly describe the historical context and research perspectives regarding this wreck. Abstract : 火星号 (1564)༚一-伟大的16世纪瑞典军舰的初步考古学调查 瑞典军舰火星号在1564年对抗丹麦与吕贝克的联合舰队时爆炸并沉没, 在此之前, 它是世界上最大的舰船-一。2011年, 沉船在波罗的海奥兰岛附近-重新定位。由于在咸水中的有利条件, 大约三分之二的船-保留在海床上, 包括了船尾与大型艉楼。本文目的是介绍自2011年以来初步的考古学观察及工作结果。我们简要描述了关于-艘沉船的历史背景及研究视角。 火星號 (1564)༚一-偉大的16世紀瑞典軍艦的初步考古學調查 瑞典軍艦火星號在1564年對抗丹-與呂貝克的聯合艦隊時爆炸並沈沒, 在此之前, 它是世界上最大的艦船-一。2011年, 沉船在波羅的海奧蘭島附近-重新定位。由于在鹹水中的有利條件, 大約三分之二的船-保留在海床上, 包括了船尾與大型艉樓。本文目的是介紹自2011年以來初步的考古學觀察及工作結果。我們簡要描述了關于-艘沉船的曆史背景及研究視角。